Corrosion Inhibition of Elettarai cardamom Bark Extract on Mild Steel in 1M H2SO4 - Gupta, Dipak Kumar; Acharya, Anuja; Yadav, Brahamdeo; Yadav, Amar Prasad (Cognition, 2023)
Elettaria cardamom (Alaichi) is a spice available in Nepal, from the bark of which alkaloid can be extracted to use as a corrosion inhibitor. The corrosion inhibition of methanolic extract of Elettaria cardamom (EC) for mild steel (MS) in 1M H2SO4 was studied using the weight loss method. The effect of time of immersion and concentration of EC extract on corrosion inhibition was investigated. The result showed that the corrosion inhibition efficiency increased with an increase in the time of immersion and concentration of the EC extract. The maximum inhibition efficiency of 1000 ppm EC extract was 93.36% for 3 hours of immersion in 1M H2SO4 solution. FTIR spectroscopic analysis showed the presence of functional groups containing oxygen and nitrogen in the extract, which is responsible for the adsorption of the extract onto mild steel and reduces the corrosion rate.